The Effect of Phase Change Material (PCM) on Efficiency and Productivity in Tubular Solar Distillation Using a Parabolic Trough Collector - Miftanul Syubban, Teuku; Amin, Muhammad; Azuar Rizal, Teuku (Fakultas Teknik Universitas Samudra, 2025)
This study investigates the effect of Phase Change Material (PCM) on temperature, efficiency, and productivity. The prototype solar distillation system is tube-shaped, with a length of 50 cm and a diameter of 4 inches, using a parabolic trough collector. The PCM used is beeswax, which is wrapped in aluminum foil. The results show that the use of PCM improves freshwater productivity. On the first day, the PCM method showed an 11% increase in production, and on the second day, freshwater production increased by 13%. The production rate with PCM was 0.76 L/m²/day, compared to the conventional method, which had a rate of 0.67 L/m²/day. The system with PCM also achieved high efficiency, reaching 11,47% on the first day and 13,9% on the second day. The system remained stable in the afternoon and evening, maintaining temperatures above 35 °C at night, compared to the system without PCM, where the temperature dropped to 30 °C. The use of PCM significantly enhanced the overall performance of the distillation system.